KETERKAITAN PENILAIAN FORMATIF DENGAN HASIL BELAJAR IPA SETELAH MENGONTROL PENGETAHUAN AWAL SISWA - Nasution, Mariam (Logaritma : Jurnal Ilmu-ilmu Pendidikan dan Sains, 2015)
Formative assessment is the evaluation conducted at the end of the discussion of a subject/ topic, and is intended to determine the extent to which the learning process has been running as planed. In assessing the formative test a science teacher in the learning process must run in certain situations. Therefore in the learning process students should have early knowledge base or IPA as a condition for getting Knowledge to a higher level. With prior knowledge of the students in science teaching and learning process, the teacher can assess the results of their study. From the results of this evaluation will be obtained picture of anyone who has been successful and who is considered to have not managed to take further appropriate actions. Learning outcomes that occur because of changes in student behavior that can be observed and measured in terms of changers in knowledge, attitudes and skills. In learning science learning outcomes can be measured by the ability of the students themselves gain knowledge about the natural environment, develop skills, insight, and awareness of the technology in relation to their use for everyday life.